Emergency department blood alcohol level associates with injury factors and six-month outcome after uncomplicated mild traumatic brain injury. (November 2017) - Yue, John K.; Ngwenya, Laura B.; Upadhyayula, Pavan S.; Deng, Hansen; Winkler, Ethan A.; Burke, John F.; Lee, Young M.; Robinson, Caitlin K.; Ferguson, Adam R.; Lingsma, Hester F.; Cnossen, Maryse C.; Pirracchio, Romain; et al.
Highlights: Day-of-injury blood alcohol level (BAL) from 107 mTBI patients with negative brain CT. BAL ≥ 80-mg/dl (U.S. legal limit) vs. BAL < 80-mg/dl cohorts for comparative analysis. Higher BAL associated with decreased GCS score and increased LOC duration. BAL ≥ 80-mg/dl associated with higher odds of impaired six-month functional recovery. BAL ≥ 80-mg/dl associated with decreased six-month nonverbal processing speed. Abstract: The relationship between blood alcohol level (BAL) and mild traumatic brain injury (mTBI) remains in need of improved characterization. Adult patients suffering mTBI without intracranial pathology on computed tomography (CT) from the prospective Transforming Research and Clinical Knowledge in Traumatic Brain Injury Pilot study with emergency department (ED) Glasgow Coma Scale (GCS) 13–15 and recorded blood alcohol level (BAL) were extracted. BAL ≥ 80-mg/dl was set as proxy for excessive use. Multivariable regression was performed for patients with six-month Glasgow Outcome Scale-Extended (GOSE; functional recovery) and Wechsler Adult Intelligence Scale Processing Speed Index Composite Score (WAIS-PSI; nonverbal processing speed), using BAL ≥ 80-mg/dl and <80-mg/dl cohorts, adjusting for demographic/injury factors. Overall, 107 patients were aged 42.7 ± 16.8-years, 67.3%-male, and 80.4%-Caucasian; 65.4% had BAL = 0-mg/dl, 4.6% BAL < 80-mg/dl, and 30.0% BAL ≥ 80-mg/dl (range 100–440-mg/dl). BAL differed across loss of consciousness (LOC; none: median 0-mg/dl [interquartile range (IQR) 0–0], <30-min: 0-mg/dl [0–43], ≥30-min: 224-mg/dl [50–269], unknown: 108-mg/dl [0–232]; p = 0.002). GCS < 15 associated with higher BAL (19-mg/dl [0–204] vs. 0-mg/dl [0–20]; p = 0.013). On univariate analysis, BAL ≥ 80-mg/dl associated with less-than-full functional recovery (GOSE ≤ 7; 38.1% vs. 11.5%; p = 0.025) and lower WAIS-PSI (92.4 ± 12.7, 30th-percentile vs. 105.1 ± 11.7, 63rd-percentile; p < 0.001). On multivariable regression BAL ≥ 80-mg/dl demonstrated an odds ratio of 8.05 (95% CI [1.35–47.92]; p = 0.022) for GOSE ≤ 7 and an adjusted mean decrease of 8.88-points (95% CI [0.67–17.09]; p = 0.035) on WAIS-PSI. Day-of-injury BAL > 80-mg/dl after uncomplicated mTBI was associated with decreased GCS score and prolongation of reported LOC. BAL may be a biomarker for impaired return to baseline function and decreased nonverbal processing speed at six-months postinjury. Future confirmatory studies are needed.